Quote Originally Posted by Jhevon View Post
$\displaystyle \begin{array}{lll} 1. & (P \wedge T) \implies (R \vee S) & \\
2. & Q \implies (U \wedge T) & \\
3. & U \implies P & \\
4. & \neg S & \backslash \therefore Q \implies R \\
5. & Q & \text{assumption} \\
6. & U \wedge T & \text{2,5 M.P.} \\
7. & U & \text{6, Simp.} \end{array}$
$\displaystyle
\begin{array}{lll}
8. & T & \text{6, Comm., Simp.} \\
9. & P & \text{3,7 M.P.} \\
10. & P \wedge T & \text{8,9 Conj.} \\
11. & R \vee S & \text{1, 10 M.P.} \\
12. & R & \text{4,11 Comm., D.S.} \\
\hline 13. & Q \implies R &

\end{array}$
By what law of logic do you justify line 13 of your proof?